2023
DOI: 10.1007/s10484-023-09595-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Neurofeedback Modulating Neural Activity in the Mesial Temporal Lobe During Memory Encoding: A Pilot Study

Abstract: Removal of the mesial temporal lobe (MTL) is an established surgical procedure that leads to seizure freedom in patients with intractable MTL epilepsy; however, it carries the potential risk of memory damage. Neurofeedback (NF), which regulates brain function by converting brain activity into perceptible information and providing feedback, has attracted considerable attention in recent years for its potential as a novel complementary treatment for many neurological disorders. However, no research has attempted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 91 publications
0
3
1
Order By: Relevance
“…Previous studies using fMRI-based bidirectional NF reported that anterograde interference could impact the latter half NF sessions [ 74 ]. This might explain discrepancies between the present and our prior study, where we performed NF using intracranial electrodes and observed increased theta power in one participant [ 24 ]. In the present study, despite the same electrode location for P02, we found NF signal values decreased over sessions for both Down and Up conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous studies using fMRI-based bidirectional NF reported that anterograde interference could impact the latter half NF sessions [ 74 ]. This might explain discrepancies between the present and our prior study, where we performed NF using intracranial electrodes and observed increased theta power in one participant [ 24 ]. In the present study, despite the same electrode location for P02, we found NF signal values decreased over sessions for both Down and Up conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, in this study, we employed a frequency band ranging from 0.5 to 32 Hz for the computation of total power, excluding any frequency bands above 32 Hz. According to previous studies, high gamma bands over 32 Hz have been reported to be implicated in memory functions, similar to theta [ 24 , 57 , 70 ]. However, here, as we particularly focused on the low theta band as a frequency band related to memory encoding, we determined that including frequencies above 32 Hz in the total power computation could potentially influence neurofeedback.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations